Tropical living : - Reyes, Elizabeth (Periplus Editions, 2000)
These books use beautiful color photographs to reveal the interiors of homes found in their respective countries. Private Sydney and South Africa provide a glimpse at contemporary interior design as practiced in each place, in some cases incorporating items from the native locale. Tropical Living and Contemporary Thai highlight the vernacular furniture, fabric, floor coverings, and decorative accessories of their respective countries in addition to showing contemporary interiors. Purchase where there is an interest in contemporary interior design.